A tumor profile in Edwards syndrome (trisomy 18). Issue 3 (30th July 2016) - Satgé, Daniel; Nishi, Motoi; Sirvent, Nicolas; Vekemans, Michel
Abstract : Constitutional trisomy 18 causes Edwards syndrome, which is characterized by intellectual disability and a particular set of malformations. Although this condition carries high mortality during prenatal and early postnatal life, some of the rare infants who survive the first months develop benign and malignant tumors. To determine the tumor profile associated with Edwards syndrome, we performed a systematic review of the literature. This review reveals a tumor profile differing from those of Down (trisomy 21) and Patau (trisomy 13) syndromes. The literature covers 45 malignancies: 29 were liver cancers, mainly hepatoblastomas found in Japanese females; 13 were kidney tumors, predominantly nephroblastomas; 1 was neuroblastoma; 1 was a Hodgkin disease; and 1 was acute myeloid leukemia in an infant with both trisomy 18 and type 1 neurofibromatosis. No instances of the most frequent malignancies of early life—cerebral tumors, germ cell tumors, or leukemia—are reported in children with pure trisomy 18. Tumor occurrence does not appear to correlate with body weight, tissue growth, or cancer genes mapping to chromosome 18. Importantly, the most recent clinical histories report successful treatment; this raises ethical concerns about cancer treatment in infants with Edwards syndrome. In conclusion, knowledge of the Edwards' syndrome tumor profile will enable better clinical surveillance in at‐risk organs (i.e., liver, kidney). This knowledge also provides clues to understanding oncogenesis, including the probably reduced frequency of some neoplasms in infants and children with this genetic condition. © 2016 Wiley Periodicals, Inc.